2015 ASEE Annual Conference and Exposition Proceedings
DOI: 10.18260/p.24214
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Sources of Information That Students Use in Deciding Which Engineering Major to Pursue

Abstract: Raised in South Florida, born in Mexico. Half Colombian and half Mexican; proud Mexilombian. Héctor is currently pursuing an MS in Computer Engineering and a PhD in Engineering Education, both from Purdue University. His research interests are in investigating the LGBTQ+ community with relation to STEM. He's an avid videographer, eater of tasty food, moped enthusiast, and user/tweaker of computers. His research interests are focused on the practice and teaching of process design, simulation and control and als… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 5 publications
0
13
0
Order By: Relevance
“…One recent study showed that approximately 70% of all first-year engineering students select a different engineering major at the end of their first year of engineering than they had originally intended 10 ; our survey of first-year non-civil engineering students indicated a similar number of non-civil engineering students having decided their major during their first year (65%). These results suggest that perhaps civil engineering students are, as a whole, more sure of their major choice (since fewer civil engineers switch majors during the first year than first-year engineering students as a whole).…”
Section: Importance Of First-year Engineering In Recruitingmentioning
confidence: 54%
See 2 more Smart Citations
“…One recent study showed that approximately 70% of all first-year engineering students select a different engineering major at the end of their first year of engineering than they had originally intended 10 ; our survey of first-year non-civil engineering students indicated a similar number of non-civil engineering students having decided their major during their first year (65%). These results suggest that perhaps civil engineering students are, as a whole, more sure of their major choice (since fewer civil engineers switch majors during the first year than first-year engineering students as a whole).…”
Section: Importance Of First-year Engineering In Recruitingmentioning
confidence: 54%
“…Our survey to second-year students who chose civil engineering, indicated "Self-led Exploration" was one of the top influencers for their decision. This was introduced by Rodriguez-Simmons et al 10 . It is worth noting that 5 of the top 6 influencers listed were attributes of the person and/or civil engineering, while self-led exploration is really a method of discovery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…15 Other sources of information that students commonly use to decide on a discipline include personal exploration, peer discussion, and advice from professors. 16 Primary difference between majors in the first year have been classified for civil, environmental, and mechanical. Students entered civil engineering to build things, environmental engineering to help the environment, and mechanical engineering because they like math and science.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Similar to first-year courses at other engineering schools [1][2][3] , the various disciplines have typically been presented to the students through department seminars in which faculty from each of the engineering departments give presentations to students. Our department is currently re-vamping the Introduction to Engineering course and has added some activities to see if it would help students decide their choice of major within the first semester or year rather than later in the student's engineering program.…”
Section: Introductionmentioning
confidence: 99%